Diseño de hardware in the loop para control de flujo. - Flores Llugcha, Luis Esteban (2021)
The project presents the Hardware-in-the-Loop (HIL) design for flow control. It consists of the interaction of real and virtual components. The virtual components are related to the simulation of control stations through MatLAb software in this case, which emulates the real behavior allowing to obtain the same benefits as a physical instrument. Prepared by means of a Data Acquisition Card, for sending and receiving electrical signals from our PID controller, through the MatLab software with its Simulink extension, a block is entered containing the transfer function, where a control variable (CV ), and as a result we will have a process variable (PV), these signals are sent back to the Acquisition Board where a PWM signal is obtained, which we will convert into an analog signal through a filter in a range of (0-5v) , and can be sent to our S7-1200 PLC controller, a Simulink executable is created to communicate with the Guide extension, where a graphical interface is created for the simulation of the flow system, thus fulfilling a normal cycle as if it were a physical module, and with a minimum economic cost in relation to a real plant.